2019
DOI: 10.1038/s41467-019-09073-5
|View full text |Cite
|
Sign up to set email alerts
|

Social networks and risk of delayed hospital arrival after acute stroke

Abstract: Arriving rapidly to the hospital after a heart attack or stroke is critical for patients to be within time windows for treatment. Prior research in heart attacks has suggested a paradoxical role of the social environment: those who arrive early are surrounded by nonrelatives, while those who arrive late are surrounded by spouses or family members. Here, we used network methods to more deeply examine the influence of social context in stroke. We examined the relationship of personal social networks and arrival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(47 citation statements)
references
References 28 publications
5
42
0
Order By: Relevance
“…with only one family member) may maintain the patient in a 'waitand-see'-behaviour. 30 Two studies by Faiz et al 9,31 explored the reasons for prehospital delay and 'decision delay' in acute stroke, but did not include interpretation of seriousness. They collected information on the patients' knowledge of stroke, but no association was found to delay when comparing patients with and without previous stroke knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…with only one family member) may maintain the patient in a 'waitand-see'-behaviour. 30 Two studies by Faiz et al 9,31 explored the reasons for prehospital delay and 'decision delay' in acute stroke, but did not include interpretation of seriousness. They collected information on the patients' knowledge of stroke, but no association was found to delay when comparing patients with and without previous stroke knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…This study was carried out at a single institution located in a densely populated area, which may offset the time difference. Factors other than cohabitation may also be relevant, with one study showing that small and close-knit social networks had a delayed hospital arrival because of restricted information flow that reinforced the norm of watch-and-wait [12]. The frequencies of administration of tPA and execution of mechanical thrombectomy did not differ between the three groups, which supports the hypothesis that the influence of cohabitation status on worsening mRS scores may be independent of both the time from the stroke onset to arriving at the hospital and the initial treatments performed.…”
Section: Discussionmentioning
confidence: 99%
“…Social networks also highlight the role of nonprofessional caregivers who are especially important over the course of neurologic illness. Social network characteristics have been shown to contribute to the likelihood of accessing acute stroke care in a timely fashion 9 as well as outcomes of stroke recovery. 3,10 It has further been shown that stroke survivors are likely to have unmet social support needs in the years following their stroke.…”
Section: Introductionmentioning
confidence: 99%
“…20 Perhaps counterintuitively, individuals with more constrained social networks have been shown to be at greater risk of delayed presentation to medical care after an acute stroke, likely owing to restricted information flow and a tendency of patients to negotiate with close network ties for delays in access to care in the setting of a medical emergency. 9 Compositional metrics captured by PERSNET include demographic and health-related characteristics among the network members, such as sex, race, smoking, alcohol use, and regular exercise (a comprehensive list is provided in Table 1). For example, PERSNET has previously been used among a cohort of patients at risk of multiple sclerosis (MS) to demonstrate a positive association between the percentage of network members deemed to have a negative health influence on the index patient and self-reported MS-related disability, 19 potentially reflecting the influence of health milieu on individual health parameters.…”
Section: Introductionmentioning
confidence: 99%